British Corporation Finance/The Development of the Business Corporation in England (Book). - Kincaid, E. A. (The Accounting Review, 1937)
Reviews two books on finance. "British Corporation Finance, 1775-1850," by G.H. Evans; "The Development of the Business Corporation in England," by Carleton Hunt.